2017
DOI: 10.1200/jgo.2016.005355
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Bad News in Ethnic Settings: Perspectives of Patients and Families in Northern Sri Lanka

Abstract: PurposeThe discussion of a cancer diagnosis and prognosis often is difficult. This study explored the expectations of Tamil-speaking patients with cancer and their families with respect to receiving their cancer diagnosis in northern Sri Lanka.MethodsThis exploratory, descriptive, qualitative study used semistructured interviews.ResultsThematic analysis identified two major themes: communication and information seeking. The findings illustrate a discrepancy between patient preference for direct disclosure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Healthcare professionals' tendency toward partial disclosure or non-disclosure is not compatible with most Asian patients' reported preference for truth-telling communication. [61][62][63][64] Our study thus provides further confirmation of the fact that clarifying patients' understanding of their illness (including prognosis) by encouraging truthtelling communication is an important prerequisite for engagement in advance care planning.…”
Section: Discussionsupporting
confidence: 65%
“…Healthcare professionals' tendency toward partial disclosure or non-disclosure is not compatible with most Asian patients' reported preference for truth-telling communication. [61][62][63][64] Our study thus provides further confirmation of the fact that clarifying patients' understanding of their illness (including prognosis) by encouraging truthtelling communication is an important prerequisite for engagement in advance care planning.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have demonstrated that there are many benefits of diagnosis disclosure for cancer patients . Despite the low diagnosis disclosure rate in Asian countries, many studies have found that a majority of patients with a terminal illness want to know the truth . Our former study also found that cancer patients' views of diagnosis disclosure were different from those of their family members.…”
Section: Introductionmentioning
confidence: 53%
“…[11][12][13] Despite the low diagnosis disclosure rate in Asian countries, many studies have found that a majority of patients with a terminal illness want to know the truth. [14][15][16] Our former study also found that cancer patients' views of diagnosis disclosure were different from those of their family members. Physicians in China should realize the different attitudes toward CDD between patients and family members.…”
Section: Introductionmentioning
confidence: 76%
“… 6 It is not the same thing in the non-Western countries. 7 , 8 Ruhnke et al’s study found that different from American patients, Japanese did not demand the cancer diagnosis be completely disclosed. 9 Patients in Saudi Arabia would prefer the family to be informed to assist them in taking treatment-related decisions.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 10 Rajasooriyar et al’s recent study found that in Sri Lanka, although patients and their family members’ views and expectations of the disclosure of diagnosis and prognosis differed, a majority of patients wanted to be told directly about their diagnosis rather than to learn of it from a relative. 8 Limited studies have been conducted on cancer patients’ preference for diagnosis disclosure in China. Thus, it is necessary to know the Chinese patients’ preference regarding diagnosis disclosure in order to provide recommendations that could be given to physicians.…”
Section: Introductionmentioning
confidence: 99%